What makes us good inventors? - Kentrotis, Konstantinos (Cranfield University, 2018)
3 Minute Thesis presented at the Cranfield Doctoral Network Annual Event 2018.Contemporary western-style toilets require a large quantity of clean water and an integrated sewage system to operate, but 2.3 billion people remain without access to improved sanitation. For this part of the globe’s population, a waterless and energy-neutral toilet would constitute a solution with high potential. An important piece of this toilet is a technology which dewaters and dries human faeces so that it can be further processed by the system. At the moment, such a technology with low requirements in terms of size, energy and power demands does not exist. This research work concerns the design and development of a technology, which aims at filling this gap. It also deals with the analysis and dissemination of any insights that derived throughout the invention process. These insights can constitute a significant contribution to knowledge for the design community and the concerned development teams, as most of the data of similar nature remain anecdotal or lack of systematic description and explanation. The first part of the PhD focuses on the design, development and testing of a novel drying technology ('dryer') for in situ, small-scale faecal sludge treatment. The contribution to knowledge of this first part lies on a novel technology (patent pending) of significant value to the operation of the Nano membrane toilet. The second part of the research aims at providing a better understanding of the cognitive processes behind design and scientific discoveries, relying on modern design theory and using the development of the dryer as a case study. More precisely, the invention described in the first part is classified using contemporary design theory and the findings are then linked to other patented designs. The third and last part of the research concerns the design and execution of the first 'Generativity test', which aims at the identification of important characteristics regarding a certain design technique which has been found to be present at many patented technologies, including the dryer. In summary, the research gaps that this work aspires to fill is the lack of suitable drying technology for a waterless and energy-neutral toilet and the lack of theoretical framework to better understand and describe how design can complement science when developing breakthrough innovations.
Keywords: design theory'; 'invention'; 'nanomembrane toilet'; 'CranfieldDN2018'; 'Design'; 'Design Innovation'